PENGGUNAAN MOBILE ASSISTED LANGUAGE LEARNING (MALL) DALAM MENGAJAR KETERAMPILAN MENDENGAR DAN BERBICARA SISWA - Ues Athoillah (Jurnal Guru Dikmen dan Diksus, 2022)
This research is aimed to investigate is there any significant effect of using Mobile Assisted Language Learning (MALL) towards students’ listening and speaking skill on the eleventh grade of SMAN 1 Tirtayasa in academic year 2020-2021. The population is the second grade students of SMAN 1 Tirtayasa. The sample of the research is two classes. They are XI IPA 1 as the controlled class and XI IPA 3 as experimental class. It was conducted by using experimental research design. The experimental group was taught by using Mobile Assisted Language Learning (MALL) through Talk English Application (TEA) which is connected to the smartphone, while the controlled group was taught by using conventional technique. The instrument was used to collect the data by answering the questions of listening and make conversation video in pair for speaking. After analyzing the data, it was found that there was significant different effect between the class which taught by using MALL and the class taught by conventional with paired sample t-test. The result of the test shows a significance value of 2 tailed 0.000 <0.05. It means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. The score of the result that teaching by using Mobile Assisted Language Learning (MALL) was higher than taught conventional. Then, the researcher confirmed the findings of the learning outcomes by using MALL besides being able to develop students' listening and speaking skills, Students have easier access to material about daily conversation. Students are assisted by an application that is integrated into their smartphones, an application that guides learning English interactively. Students also can hone their listening and speaking skills at the same time because in learning using Talk English Application (TEA) students are trained to understand the speaker's expressions and respond to what the speaker says.